2020
DOI: 10.1111/1440-1681.13437
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D2 inhibition alleviates diabetic hepatic stellate cells fibrosis by regulating the TGF‐β1/Smads and NFκB pathways

Abstract: Diabetic hepatic fibrosis (DHF) is a progressive liver disease and a chronic complication of diabetes mellitus. The main cause of DHF is the activation of quiescent hepatic stellate cells (HSCs) by high glucose stimulation. Dopamine receptor D2 (DRD2)‐mediated dopamine signalling can be involved in the regulation of diabetic liver disease, but the exact role of DRD2 in DHF is still poorly understood. This study aimed to investigate the protective effect of DRD2 inhibition on diabetic liver fibrosis and the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…It has been previously suggested that dopamine receptor D2 antagonists, such as, prochlorperazine dimaleate, exert anti-fibrotic effects in models of diabetic hepatic fibrosis and non-alcoholic steatohepatitis induced liver fibrogenesis by regulating TGF-β1/Smad in hepatic stellate cells, and decreasing YAP levels in macrophages, respectively [ 59 , 60 ]. To our knowledge this pathway has not been investigated in PD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that dopamine receptor D2 antagonists, such as, prochlorperazine dimaleate, exert anti-fibrotic effects in models of diabetic hepatic fibrosis and non-alcoholic steatohepatitis induced liver fibrogenesis by regulating TGF-β1/Smad in hepatic stellate cells, and decreasing YAP levels in macrophages, respectively [ 59 , 60 ]. To our knowledge this pathway has not been investigated in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al. found that DRD2 can be inhibited by TGF‐β1/Smarts and that the NF‐κB pathway partially reduces oxidative damage and the proliferation of hepatic stellate cells (HSCs) in diabetes 87 . Yan et al.…”
Section: Roles Of Dopamine and Dopamine Receptors In Liver Diseasementioning
confidence: 99%
“…activation inactivated YAP/TAZ, switching activated fibroblasts from a fibrotic state of contraction, proliferation and matrix deposition to a matrix degradation-promoting state, thereby reversing liver fibrosis 86. Zhao et al found that DRD2 can be inhibited by TGF-β1/Smarts and that the NF-κB pathway partially reduces oxidative damage and the proliferation of hepatic stellate cells (HSCs) in diabetes 87. …”
mentioning
confidence: 99%
“…Another enzyme, CAT, accelerates the decomposition of H 2 O 2 into water and molecular oxygen ( Yan, Chen, & Zheng, 2017 ; B. B.; Zhao et al, 2021 ). Excessive blood glucose can hinder the antioxidant defense system, which influences the actions of antioxidant cascade enzymes in DM conditions (H. Q.…”
Section: Oxidative Stress Mechanistic Features In Diabetic Neuropathymentioning
confidence: 99%